2018
DOI: 10.3168/jds.2018-14594
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics of Lactococcus lactis F44 under cross-stress of low pH and lactate

Abstract: Lactococcus lactis encounters 3 environmental stimuli, H, lactate, and undissociated lactic acid, because of the accumulation of lactic acid-the predominant fermentation product. Few studies have examined how these stimuli synergistically affect the bacteria. Herein, we analyzed the dissociation degree of lactic acid at different pH and investigated the cellular response to cross-stress in L. lactis ssp. lactis F44 through quantitative proteomic analysis using isobaric tags for relative and absolute quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…We speculated that the improved multi-stress tolerance of the mutant strains was owing to the loss of PRF, resulting in remodeling of the cell wall/ membrane and changes in carbon source metabolism. Previous studies have shown that the structure of the cell wall/membrane affects the nisin tolerance of LAB [45], and cell wall, as the first barrier of bacteria, is essential for the strain's stress tolerance [20]. Similarly, in the present study, the synthesis levels of enzymes related to cell wall/membrane biosynthesis and degradation in L. lactis N8-1 were noted to be altered.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We speculated that the improved multi-stress tolerance of the mutant strains was owing to the loss of PRF, resulting in remodeling of the cell wall/ membrane and changes in carbon source metabolism. Previous studies have shown that the structure of the cell wall/membrane affects the nisin tolerance of LAB [45], and cell wall, as the first barrier of bacteria, is essential for the strain's stress tolerance [20]. Similarly, in the present study, the synthesis levels of enzymes related to cell wall/membrane biosynthesis and degradation in L. lactis N8-1 were noted to be altered.…”
Section: Discussionsupporting
confidence: 75%
“…In general, deletion of non-essential genome fragments, such as prophages and transposons, could confer some advantages on bacterial strains [17], including enhanced growth, increased biomass, and higher level of proteins synthesis [18]. Besides, prophages can usually synthesize proteins like prophage lysin that affect the host cell wall/membrane [19], and cell wall/membrane is essential for maintaining cellular integrity and resisting environmental stress [20]. For instance, the structure of the cell wall/membrane of nisin-producing L. lactis can also affect its tolerance to nisin [21].…”
Section: Introductionmentioning
confidence: 99%
“…Under carbohydrate-limiting conditions, homofermentative LAB metabolize pyruvate via pyruvate formate-lyase or pyruvate dehydrogenase to formate/CO 2 , acetate, and ethanol as an alternative to lactate formation (24), with pyruvate formate-lyase being preferentially used under anaerobic conditions at nearneutral pH (59,60). In addition, downregulation of L-lactate dehydrogenase and upregulation of pyruvate formate-lyase in response to low pH and high lactate concentrations were observed in Lactococcus lactis (61). The lack of lactate production by Carnobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5A shows that arginine accounts for the highest proportion of the intracellular free amino acids. In fact, the arginine deaminase (ADI) system is considered to be an important factor to protect microbial cells against acidic environment (Senouci-Rezkallah et al, 2011;Wu et al, 2018). Besides, aspartate can be converted into arginine to participate in the ADI system, accompanied by the formation of NH 3 (FernĂĄndez and ZĂșñiga, 2006).…”
Section: Effects Of Environmental Ph On Intracellular Free Amino Acidmentioning
confidence: 99%